2005
DOI: 10.1002/ab.20107
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional predictors of sexual assault perpetration in a community sample of single African American and Caucasian men

Abstract: Computer-assisted self-interviews were completed with a random sample of 163 unmarried Caucasian and African American men in a large metropolitan area. Almost a quarter (24.5%) of these men acknowledged committing an act since the age of 14 that met standard legal definitions of attempted or completed rape; an additional 39% had committed another type of sexual assault involving forced sexual contact or verbal coercion. An expanded version of the Malamuth et al.[1991] confluence model was examined using path a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
188
3
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(204 citation statements)
references
References 76 publications
(105 reference statements)
11
188
3
2
Order By: Relevance
“…In Wheeler et al (2002), 61% of male college student participants reported that they had perpetrated some form of sexual aggression. Abbey et al (2006) found that 64% of the men in a representative community sample of young adult men in one metropolitan area reported that they had perpetrated sexual assault. Perpetration and victimization rates vary depending on how the questions are asked, what types of questions are asked, and the mode of responding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Wheeler et al (2002), 61% of male college student participants reported that they had perpetrated some form of sexual aggression. Abbey et al (2006) found that 64% of the men in a representative community sample of young adult men in one metropolitan area reported that they had perpetrated sexual assault. Perpetration and victimization rates vary depending on how the questions are asked, what types of questions are asked, and the mode of responding.…”
Section: Discussionmentioning
confidence: 99%
“…Another important construct to consider for future research is empathy. As described in the introduction, several researchers have found that empathy acts as a protective factor, interacting with impersonal sex and/or hostile masculinity to produce lower levels of sexual assault (Abbey et al, 2006;Dean & Malamuth, 1997;Wheeler et al, 2002). Furthermore, there may be other situational factors in addition to alcohol that are important to consider.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30,31,[33][34][35] In this context, empathy requires a capacity and willingness to imagine the abused child's perceptions, needs, and trauma, and right to bodily inviolability, while avoiding the profound distress some have claimed decreases helping behaviour and produces self-preservation. 37 Empathy is known to be necessary to reduce sexual violence generally, 10,11 and against children in particular. 14,36,38 As a mechanism, empathy catalyzes behaviour appropriate to the needs of the person, and acts as a circuit-breaker on inappropriate impulses and harmful behaviour.…”
Section: The Need To Develop Empathy and Indications For Progressmentioning
confidence: 99%